Designing proteins with life sustaining activities 1 - Hecht, Michael (Henry Stewart Talks, 2017)
Protein design & synthetic biology, Designing novel proteins using a hybrid approach, Combinatorial libraries of novel proteins, Folding of novel proteins into stable structures, Biochemical activity of novel proteins in vitro (binding & catalysis), Essential biological functions provided by novel proteins in vivo